A proposal to regard the former family Naididae as a subfamily within Tubificidae (Annelida, Clitellata) - Erséus, C.; Gustavsson, L. (Hydrobiologia, 2002)
Following recent phylogenetic assessments using DNA data, the aquatic oligochaete family Naididae (=Naidina Ehrenberg, 1828) is proposed to be treated as a subfamily, Naidinae, within Tubificidae Vejdovský, 1876. [A complication of this proposal is that the family-group name Naididae is older than Tubificidae, and thus, according to the International Code of Zoological Nomenclature, should have precedence over the latter; this will be dealt with in a separate application to the International Commission of Zoological Nomenclature.] Naidinae appears to be closely related to taxa currently placed in another tubificid subfamily, Rhyacodrilinae, but it is argued that, while Naidinae is likely to be a natural group, Rhyacodrilinae is most probably not, neither with nor without the inclusion of the naidines. It is thus predicted that future revisions will involve splitting of Rhyacodrilinae rather than a drastic change in the circumscription of Naidinae.